Relevansi Kajian Hukum Adat : Kasus Perkawinan Anak dari Masa ke Masa - Sita Thamar van Bemmelen; Mies Grijns (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2018)
AbstractAlthough the prevalence of child marriage in Indonesia is still high, adat law studies on child marriage have not received as much attention as land-related studies. This research concerning a century of political debate on child marriage proves that child marriage can only be understood if examined from the perspective of the dynamic relationship between national law, religious law, and adat law. A comparison between the results of an antrophological case study on West Java (Sundanese and Islam) and a historical case study on North Sumatra (Toba Batak and Christian) shows that the legal culture of the community and the role of religious leaders are important determinants of the acceptance or rejection of child marriage. IntisariMeskipun prevalensi perkawinan anak di Indonesia masih tinggi, studi hukum adat terhadap perkawinan anak belum mendapat perhatian sebesar studi terkait tanah. Penelitian tentang satu abad debat politik tentang perkawinan anak ini membuktikan bahwa perkawinan anak hanya dapat dipahami bila diteliti dari sudut dinamika antara hukum negara, hukum agama dan hukum adat. Perbandingan studi kasus penelitian antropologi di Jawa Barat (suku Sunda, Islam) dan studi kasus sejarah di Sumatra Utara (suku Batak Toba, Kristen) menunjukkan bahwa budaya hukum masyarakat dan peran pemimpin agama adalah faktor penting penentu penerimaan atau penolakaan perkawinan anak.